(untitled) (Research, Society and Development, 2021)
This study deals with the necropolitical nature of discourses that function as technology of death. This is a deepening of the work of Achille Mbembe in what concerns necropolitics and necropower operating, in this case, in the field of language and discourse. The efforts carried out here converge to the conceptual elaboration of this necropolitical technology that throws the lives of some into the powers of death. For the theoretical development of this work, three concepts called here the triad of power, biopower, state of exception and necropower were used, in an attempt to sediment the notions that orbit and intersect in what I call necrodiscourse. Based on these theoretical foundations, discursive analyzes were produced of the statements made by President Jair Bolsonaro and some of his ministers, delivered during the year 2020, concerning the COVID-19 pandemic. The analyzes allowed us to understand that such discourses function as technologies of death, as they expose the lives of historically marginalized populations to existential limits, being in this sense, necrodiscourses.